Bone regeneration with platelet-rich fibrin and autologous bone graft after extracting impacted canine. Case report - Ormaza Agualsaca, Cinthya Geovanna (2021)
The objective of this case report is to assess the use of autologous bone graft and platelet-rich fibrin (FRP), as guided bone regeneration, after the extraction of a retained canine. A 42-year-old female patient, with a history of controlled hypertension, attended the SERODU dental clinic (Ecuador), due to the presence of prominence in the left nasolabial region. A Computerized Axial Tomography (CT) was performed, in which tooth 1.3 included in the maxilla was observed, in a horizontal position, the crown mesially and the root distally. It was decided to carry out the extraction of the retained canine and the placement of regenerative biomaterials based on FRP and an autologous bone graft, obtained from the right maxillary tuberosity. Clinical and radiographic controls were carried out after surgery. Six months later, adequate healing and images compatible with bone regeneration were observed in the intervened area.